N-3 Polyunsaturated Fatty Acid Dehydrogenase Fat-1 Regulates Mitochondrial Energy Metabolism by Altering DNA Methylation in Isolated Cells of Transgenic Cattle - Wang, Xueqiao; Zhu, Lin; Wei, Zhuying; Gu, Mingjuan; Yang, Miaomiao; Zhou, Xinyu; Bai, Chunling; Su, Guanghua; Liu, Xuefei; Yang, Lei; Li, Guangpeng (Frontiers in Molecular Biosciences, 2022)
The fatty acid dehydrogenase fat-1 gene, derived from Caenorhabditis elegans, encodes n-3 polyunsaturated fatty acid dehydrogenase (Δ15 desaturase) and catalyzes the 18–20-carbon n-6 polyunsaturated fatty acids (n-6 PUFA) to generate corresponding n-3 polyunsaturated fatty acids (n-3 PUFA). Subsequently, fat-1 can influence the n-6: n-3 PUFA ratio in fat-1 transgenic cells. This study aimed to explore which processes of energy metabolism are affected by increasing endogenous n-3 PUFA and the relationship between these effects and DNA methylation. Compared with the wild-type group, the n-3 PUFA content in fat-1 transgenic bovine fetal fibroblasts was significantly increased, and the n-6 PUFA content and the n-6: n-3 PUFA ratio decreased. In the context of energy metabolism, the increase of n-3 PUFA content decreased ATP synthesis by 39% and reduced the activity and expression of key rate-limiting enzymes in glycolysis, the tricarboxylic acid cycle, and oxidative phosphorylation, thus weakening the cells’ capacity for ATP production. DNA methylation sequencing indicated that this inhibition of gene expression may be due to altered DNA methylation that regulates cell energy metabolism. Endogenous n-3 PUFA in fat-1 transgenic cells increased and showed changes in the degree of methylation in the promoter region of genes related to energy metabolism rate-limiting enzymes. We suggest that endogenous increases in n-3 PUFA could regulate altered DNA methylation that affect mitochondrial energy metabolism.